A Novel 3q29 Deletion in Association With Developmental Delay and Heart Malformation—Case Report With Literature Review - Chirita Emandi, Adela; Dobrescu, Andreea Iulia; Doros, Gabriela; Hyon, Capucine; Miclea, Diana; Popoiu, Calin; Puiu, Maria; Arghirescu, Smaranda (Frontiers in Pediatrics, 2019)
3q29 deletion syndrome is a rare disorder, causing a complex phenotype. Clinical features are variable and relatively nonspecific. Our report aims to present an atypical, de novo deletion in chromosome band 3q29 in a preschool boy, first child of healthy non-consanguineous parents, presenting a particular phenotype (microcephaly, "full moon" face, flattened facial profile, large ears, auricular polyp and dental dystrophies), motor and cognitive delay, characteristics of autism spectrum disorder and aggressive behavior. He also presented intrauterine growth restriction (birth weight 2400 g) and ventricular septal defect. SNP Array revealed a 962 kb copy number loss, on chromosome 3q29 band (195519857-196482211), consistent with 3q29 microdeletion syndrome. FISH analysis using RP11-252K11 probe confirmed the deletion in proband, that was not present in the parents. Although the patient’s deletion is relatively small, it partly overlaps the canonical 3q29 deletion (defined between TFRC and DLG1 gene) and extends upstream, associating a different facial phenotype compared to the classic 3q29 deletion, nonetheless showing similar psychiatric disorder. This deletion is different from the canonical region, as it does not include the PAK2 and DLG1 genes, considered as candidates for causing intellectual disability. Thus, narrowing the genotype-phenotype correlation for the 3q29 band, FBX045 is suggested as a candidate gene for the neuropsychiatric phenotype.